DIGITAL FINANCIAL TRANSACTION MANAGEMENT EDUCATION TO IMPROVE THE EFFICIENCY OF MICRO-ENTERPRISES IN THE TOURISM AREA TETEBATU, SIKUR, EAST LOMBOK - Afrida Nur Chasanah; Baiq Herdina Septika; Miratul Husna Neris; Ridho Rafqi Ilhamalimy; Menik Aryani (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT The growing use of digital transactions in the tourism sector has encouraged business actors to adapt their services to increasingly cashless payment systems. However, this shift has not been fully embraced by micro, small, and medium enterprises (MSMEs) in South Tetebatu Tourism Village, where limited digital financial literacy, dependence on cash transactions, and inadequately documented transaction management remain prevalent challenges. In response to these conditions, this community service program was designed to strengthen MSME capacity in utilizing digital financial services while promoting the implementation of the Quick Response Code Indonesian Standard (QRIS) as a more efficient transaction method. A Participatory Action Research (PAR) approach was employed through a series of activities, including partner needs assessment, digital financial literacy education, QRIS registration and installation assistance, and hands-on practice in the use of digital transactions within business settings. The program demonstrated that MSME actors responded positively to cashless payment systems and were able to operate QRIS in their daily business activities. The assistance provided not only facilitated the creation of digital wallet accounts and the implementation of QRIS but also enhanced the use of transaction histories as part of a more structured business management process. These findings indicate that the adoption of digital payment technology becomes more effective when literacy enhancement, technical assistance, and practical experience are developed in an integrated manner. The integration of these three components contributes to strengthening financial inclusion, improving digital transformation readiness, and developing an MSME empowerment model that supports the competitiveness of community-based tourism destinations. ABSTRAK Perkembangan transaksi digital di sektor pariwisata mendorong pelaku usaha untuk menyesuaikan pola layanan yang semakin mengarah pada sistem pembayaran nontunai. Kondisi tersebut belum sepenuhnya diikuti oleh pelaku usaha mikro, kecil, dan menengah (UMKM) di Desa Wisata Tetebatu Selatan yang masih menghadapi keterbatasan literasi keuangan digital, dominasi transaksi tunai, serta pengelolaan transaksi yang belum terdokumentasi secara optimal. Berangkat dari kebutuhan tersebut, kegiatan pengabdian ini dirancang untuk memperkuat kapasitas pelaku UMKM dalam memanfaatkan layanan keuangan digital sekaligus mendorong penerapan Quick Response Code Indonesian Standard (QRIS) sebagai sarana transaksi yang lebih efisien. Pendekatan Participatory Action Research (PAR) digunakan melalui rangkaian kegiatan yang meliputi identifikasi kebutuhan mitra, edukasi literasi keuangan digital, pendampingan registrasi dan pemasangan QRIS, serta praktik langsung penggunaan transaksi digital pada lingkungan usaha. Pelaksanaan program menunjukkan bahwa pelaku UMKM memberikan respons positif terhadap penggunaan sistem pembayaran nontunai dan mampu mengoperasikan QRIS dalam aktivitas usaha sehari-hari. Pendampingan yang dilakukan tidak hanya memfasilitasi pembuatan akun dompet digital dan implementasi QRIS, tetapi juga meningkatkan pemanfaatan riwayat transaksi sebagai bagian dari pengelolaan usaha yang lebih terstruktur. Temuan ini mengindikasikan bahwa adopsi teknologi pembayaran digital menjadi lebih efektif ketika peningkatan literasi, pendampingan teknis, dan pengalaman praktik dikembangkan secara terpadu. Integrasi ketiga aspek tersebut berkontribusi pada penguatan inklusi keuangan, peningkatan kesiapan transformasi digital, serta pengembangan model pemberdayaan UMKM yang relevan untuk mendukung daya saing kawasan wisata berbasis masyarakat.